Adaptation of broccoli (Brassica oleracea var. italica L.) to high and low altitudes in Bali, Indonesia - Ida Ayu astarini (MBI & UNS Solo, 2020)
Abstract. Astarini IA, Defiani MR, Suriani NL, Griffiths PD, Stefanova K, Siddique KHM. 2020. Adaptation of broccoli (Brassica oleracea var. italica L.) to high and low altitudes in Bali, Indonesia. Biodiversitas 21: 5263-5269. Broccoli is an important vegetable worldwide, with expanding markets and opportunities in Asia. In Indonesia, there is demand from high-end hotels, restaurants, and export markets, but the local supply is low quality and low yielding. Crown cuts are typically small and misshapen as the varieties are grown are not adapted to local environments. This study targeted new broccoli varieties to identify those best adapted to environmental stresses in Bali, Indonesia, using two-site replicated field experiments. Experiments were undertaken in two regions in Bali (Bedugul and Tabanan) using 13 commercial varieties that included heat-sensitive varieties and others identified as heat-tolerant in trials on the East Coast of the USA. The trials evaluated the varieties for crown initiation, days to maturity, crown size at harvest, crown diameter, and overall performance. The study demonstrated that all 13 varieties could be used for broccoli production in the Bedugul region (1200 m a.s.l. altitude), with Castle Dome being the best performer due to its earlier maturity and large high-quality crown. The varieties Bay Meadows, Belstar, Imperial, and Sarasota could be used in the Tabanan region.